Prevalence and Risk Factors of Potential Drug-Drug Interactions in the In-Patient Medical Wards: A Hospital-Based Cross-Sectional Study: Pharmaceutical Science-Pharmacy practice - Samhitha Reddy, Y; Somasekhar Reddy , K (International Journal of Life Science and Pharma Research, 2022)
Evidence shows that half of the Adverse Drug Reactions (ADRs) resulting from Drug-Drug Interactions (DDI) are predictable and preventable. Hospitalized patients are more expected to develop DDI. The current study aims to assess the prevalence, risk factors, and severity of PDDIs among hospitalized patients. This is a cross-sectional study that was conducted in medical wards of a NGO charity hospital located in Bathalapalli, Anantapur district. Patients aged 18 years or more, and admitted to the in-patient medical wards taking more than one medication have been selected for the study. A total of 310 subjects who met the study criteria were enrolled in the study after taking oral and written informed consent. Patient demographics, a list of medications, and clinical characteristics were collected from admission to discharge by the review of medical records and patient interviews. The collected data were subjected to identify and grade the severity of PDDI by using IBM Micromedex® Drug Interaction Checker. Among 310 in-patients, 82 cases had 127 PDDI with a prevalence of 26.45%. The majority of the PDDI are moderate (57; 44.9%) in severity level. Factors like the advanced age group of more than 40 years, more than one comorbidity, staying in the hospital for more than four days, and more than five drugs per prescription were positively associated with having PDDI with a P value less than 0.05. Clinical pharmacists need to work with the healthcare team to provide interventions to reduce clinically significant interactions and improve clinical outcomes.